Plants for biophilic design in green building - Kryvomaz, Тetiana; Tyshchenko, Oksana; Suleimanov, Ismet (Theory and practice of design, 2022)
The article explores the ways of using plants for biophilic design in green building. Target. To identify current directions for the practical application of the biophilic design principles in the context of green building by specialists in the field of construction, architecture and landscape design to improve the built environment and urbanized space. Methodology. Innovative green building technologies and biophilic design principles. Results. Modern trends in the development of green building and biophilic design are analyzed and areas of intersection of both concepts are identified. They are closely related to protecting the health and safety of people, improving the quality and comfort of the built environment, and nature protection. Both technologies also imply the functional and aesthetic use of plants. The prospects and risks of using plants in urban areas are assessed. Perspective directions for the development of biophilic design in accordance with the concept of green building have been established. Scientific significance. The general social, environmental and economic benefits of green building and biophilic design are identified. It has been established that as a result of the use of these technologies, the comfort of living is increased even in conditions of increased density in urban areas. Promising directions of biophilic methods are identified in accordance with the international trend of green transformation of cities due to pandemic threats. Practical significance. Lists of plant species are presented to improve the microclimate and the air cleaning of urban spaces, for vertical gardening of interiors and exteriors. The regularities of the influence of plants on the health and well-being of people are characterized. It is recommended to be guided by the requirements of functionality and safety, to maintain a rational balance between local plants and species from other regions in favor of the first.